PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS COGNITIVE LOAD THEORY (CLT) PADA MATERI VOLUME KUBUS DAN BALOK DI SEKOLAH DASAR - Rissa Prima Kurniawati; Fida Rahmantika Hadi; Vivi Rulviana (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research aims to describe the development of interactive learning multimedia based on cognitive load theory (CLT) in the fifth grade of elementary school. This type of research is research and development (R & D). The methods of collecting the data in this research were questionnaires, and interviews. This questionnaire is used to determine the response of students after using interactive multimedia based on CLT. Meanwhile this interview was conducted to find out the responses, comments, and suggestions of teachers and students after using interactive multimedia based on CLT. The validity of the results of the validation data analysis from this material expert was 87.50% and the validity of the validation data from this media expert was 85.71%. It shows that the material in CLT-based learning multimedia is valid and ready to be implemented. And the average questionnaire score at SDN 3 Taman was 88.27%, so the results of the questionnaire were declared good. The advantages of this CLT-based interactive learning multimedia are this multimedia display is very interesting, the material is presented more interesting, and the menus that are presented are easy to understand.